2012
DOI: 10.1158/1055-9965.epi-12-0848
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Prevention for Global Health: A Report from the ASPO International Cancer Prevention Interest Group

Abstract: As cancer incidence and mortality rates increase in low-and middle-income countries, the need for cancer prevention and control research directed to these countries becomes increasingly important. The American Society of Preventive Oncology (ASPO) is a community of professionals in cancer prevention and control whose mission is to "foster the continuing development of investigators and the exchange and translation of scientific information to reduce the cancer burden."In the session presented at the ASPO 36th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…However, our evaluations have shown that smoking is a lifestyle factor that shows an association with prostate cancer in the current study group. This could be related to tobacco smoke being an established carcinogen that could cause many human cancers [30,31]. …”
Section: Discussionmentioning
confidence: 99%
“…However, our evaluations have shown that smoking is a lifestyle factor that shows an association with prostate cancer in the current study group. This could be related to tobacco smoke being an established carcinogen that could cause many human cancers [30,31]. …”
Section: Discussionmentioning
confidence: 99%
“…Smoking represents a serious worldwide public health problem because of its close association with the development of chronic disease and cancer in low‐ and middle‐income countries . Despite wide knowledge on the subject, the prevalence of tobacco smoking is still high.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to an increasing U.S. cancer burden, cancer is an emerging public health challenge in developing countries because of the aging and expansion of the population and increased prevalence of cancer risk factors such as smoking, obesity, and physical inactivity [9]. While global public health efforts in developing countries have traditionally centered on the prevention and treatment of communicable diseases, the global burden of disease has been changing, with approximately 70% of worldwide deaths in 2015 due to non-communicable diseases [10].…”
Section: Cancer and Public Health In The United Statesmentioning
confidence: 99%